Society of Knowledge or Cultures of Knowing? - Mendez, Mario (2010)
The following pages present a critical approach to the claim to understand education from its adjustment to the so-called "knowledge society," "information society" or "learning society," all of which are categories frequently used to describe the type of production of wealth corresponding to post-industrial society.